2020
DOI: 10.1101/2020.11.05.351874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex population structure of the Atlantic puffin revealed by whole genome analyses

Abstract: The factors underlying gene flow and genomic population structure in vagile seabirds are notoriously difficult to understand due to their complex ecology with diverse dispersal barriers and extensive periods at sea. Yet, such understanding is vital for conservation management of seabirds that are globally declining at alarming rates. Here, we elucidate the population structure of the Atlantic puffin (Fratercula arctica) by assembling its reference genome and analyzing genome-wide resequencing data of 72 indivi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…In conclusion, our study underlines the importance of genetically informed management decisions by showing unexpected population structure as previously discovered in Iberian wolves, Peruvian diving-petrels, and Atlantic puffins, among others (Cristofari et al, 2019;Kersten et al, 2021;Silva et al, 2018). It most notably shows that land-and seascape genetics should go hand in hand because terrestrial organisms living close to the sea could be influenced by both.…”
Section: Conservation and Research Implicationssupporting
confidence: 69%
“…In conclusion, our study underlines the importance of genetically informed management decisions by showing unexpected population structure as previously discovered in Iberian wolves, Peruvian diving-petrels, and Atlantic puffins, among others (Cristofari et al, 2019;Kersten et al, 2021;Silva et al, 2018). It most notably shows that land-and seascape genetics should go hand in hand because terrestrial organisms living close to the sea could be influenced by both.…”
Section: Conservation and Research Implicationssupporting
confidence: 69%
“…grabae , and has led many to question the validity of Atlantic Puffin subspecies [ 22 , 23 ]. A recent study on population structure of the Atlantic Puffin using whole genome data [ 24 ] identified four population clusters that disagrees with the traditional view of three subspecies. This suggests that Atlantic Puffin taxonomy is more complicated than previously assumed.…”
Section: Introductionmentioning
confidence: 99%